Pengaruh Perputaran Modal Kerja Terhadap Laba - Mawaddah, Nurul; Epi, Yus (TIN: Terapan Informatika Nusantara, 2023)
This research method uses a descriptive analysis approach with the variables used being working capital turnover and profit with the research data source being secondary data. The author uses data collection techniques, namely observation and documentation in the form of financial reports (Balance Sheet and Profit and Loss) and interviews. Based on the results of research and discussions that have been carried out, it can be concluded that working capital turnover tends to increase from November - December, increasing every period, but in the August period it decreased to minus, this shows that the company's working capital has not been effective and inadequate in increasing profit at Miby Parfum Medan. And profits decreased in September, the decrease was due to increasing expenses. The decrease was due to quite high costs incurred while net profit experienced a decline.